TINGKAT KEPADATAN LALAT DAN KEPEMILIKAN JAMBAN SEHAT DENGAN KEJADIAN DIARE DI PUSKESMAS AIR HITAM LAMPUNG BARAT - -, Ahmat Arif; Putri, Dian Utama Pratiwi; Arief Hermawan, Nur Sefa (LPPMK STIKES Widyagama Husada, 2025)
Introduction: This study aims to analyse the relationship between fly density and ownership of healthy latrines to the incidence of diarrhoea at Puskesmas Air Hitam, West Lampung District. The method used was quantitative research with a cross-sectional approach, involving 88 respondents selected based on inclusion and exclusion criteria. Data were collected through interviews and direct observation, and analysed using the chi-square test to determine the relationship between variables. The results showed that out of 81 respondents, 62 (76.5%) experienced diarrhoea, while 19 (23.5%) did not. There was a significant relationship between fly density and the incidence of diarrhoea with a p value = 0.020, and an odds ratio (OR) of 2.536, indicating that the risk of diarrhoea increased with increasing fly density. In addition, ownership of healthy latrines plays an important role in preventing the spread of disease. This study emphasises the importance of improving environmental sanitation and hygiene to reduce the incidence of diarrhoea in the community..